Clinical and genetic study of a Chinese family affected by both amyotrophic lateral sclerosis and autosomal dominant polycystic kidney disease - Li, Shirong; Lin, Junyu; Li, Chunyu; Chen, Yongping; Cao, Bei; Yang, Tianmi; Wei, Qianqian; Zhao, Bi; Chen, Xueping; Shang, Huifang (Frontiers in Neurology, 2022)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder characterized by loss of the upper and lower motor neurons from the motor cortex, brainstem, and spinal cord. Most ALS cases are sporadic, with 5-10% having a positive family history. Autosomal dominant polycystic kidney disease (ADPKD) is a heritable renal disease that eventually results in end-stage kidney disease. PKD1 is the most prevalent causative gene for ADPKD, accounting for approximately 85% of cases. Both diseases are currently considered untreatable. In this study, we report a large family that includes 10 patients with ALS phenotype, 3 asymptomatic SOD1-H47R carriers and 6 with the ADPKD phenotype. Using whole exome sequencing, we found a novel likely pathogenic variant (p.R2787P) in PKD1 among patients with ADPKD, and a pathogenic variant (p.H47R) in SOD1 among patients with ALS. This study highlights the possibility that two different autosomal dominantly inherited diseases can co-exist independently within the same family. Phenotype - genotype correlations among these patients are also described. This research contributes novel phenotype and genotype characteristics of ALS with SOD1 mutations and ADPKD with PKD1 mutations.